2019
DOI: 10.33549/physiolres.934345
|View full text |Cite
|
Sign up to set email alerts
|

The PI3k/Akt Pathway Is Associated With Angiogenesis, Oxidative Stress and Survival of Mesenchymal Stem Cells in Pathophysiologic Condition in Ischemia

Abstract: Ischemic diseases are characterized by reduced blood supply to a tissue or an organ due to obstruction of blood vessels. The most serious and most common ischemic diseases include ischemic heart disease, ischemic stroke, and critical limb ischemia. Revascularization is the first choice of therapy, but the cell therapy is being introduced as a possible way of treatment for no-option patients. One of the possibilities of cell therapy is the use of mesenchymal stem cells (MSCs). MSCs are easily isolated from bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 28 publications
(15 reference statements)
2
72
0
Order By: Relevance
“…It has been well characterized that the ERK1/2 and PI3K/AKT signaling pathways are critical regulators during the apoptosis process [ 10 , 45 ]. It is important to note the crosstalk between these two signaling axes with mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well characterized that the ERK1/2 and PI3K/AKT signaling pathways are critical regulators during the apoptosis process [ 10 , 45 ]. It is important to note the crosstalk between these two signaling axes with mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is generally considered as a vital process to maintain the homeostasis of both tissues and cells, which is regulated by sophisticated apoptotic signals [ 9 ]. A mass of evidence suggests that PI3K/AKT and ERK1/2 signaling pathways are related to cell proliferation and apoptosis [ 10 12 ]. Ascending expression of AKT phosphorylation and ERK1/2 phosphorylation seems to be pivotal anti-apoptotic signals [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that all MAPK inhibitors increase the O 2 •- levels in H 2 O 2 -induced A549 cells ( 42 ). The PI3K/Akt signaling pathway is related to survival, angiogenesis and oxidative stress under pathophysiologic conditions in ischemia ( 43 ). Klotho has been shown to weaken oxidized low-density lipoprotein (ox-LDL)-induced oxidative stress in HUVECs via the upregulation of oxidative scavengers by suppressing lectin-like ox-LDL receptor expression and activating the PI3K/Akt/eNOS pathway ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, both 100 Hz and 2 Hz/10 0HZ-EA are effective in improving the recovery of hindlimb motor function in spinal cord injury (SCI) rats; this may be associated with the function of reducing neuronal apoptosis and promoting the autophagy of damaged nerve cells (Luo et al, 2019). The PI3K/AKT pathway plays an important role in regulating cell proliferation, differentiation, migration, and apoptosis in various types of cells (Samakova et al, 2019). Therefore, the PI3K/AKT pathway is a key target for ischemic stroke treatment.…”
Section: Introductionmentioning
confidence: 99%